Students' Perspective on Challenges in English Oral Presentation: A Case Study - Deby Lara Sucia M; Abdul Rohman; Widi Syahtia Pane (Wadah Inovasi Indonesia, 2023)
The anxiety of English learners who lack conviction in the classroom. In order to communicate with their tutors and peers, they need new incentives to enhance their English speaking abilities. For oral presentations to be comprehended, students must communicate well. This investigation employed qualitative approaches. The study was a case study because it focused on English Oral Presentation learning and involved numerous English students. Five English Department students who struggle with English Oral Presentation were selected via snowball sampling. The research instrument includes guidelines for semi-structured interviews and observation to capture data and information on the research topic, followed by three data analysis tasks: data compression, data presentation, and conclusion drawing or verification. This study discovered that participants' anxiety manifests itself in the following ways: difficulty explaining the topic, perusing the text rather than explaining it, and avoiding making eye contact with others. Anxiety is the greatest dread when speaking. Participants recommended studying grammar, exploring the Internet, mastering the subject, and practicing. Students labored with oral presentations in English. Separated from speaking difficulties were anxiety, self-confidence, and self-awareness. (grammatical error, switch language, read the text). The majority of students stated that anxiety and lack of confidence made English oral presentations challenging. According to their research, a number of experts have resolved student issues.